A genome-wide association study in Hispanics/Latinos identifies novel signals for lung function: the Hispanic Community Health Study/Study of Latinos - Burkart, Kristin M.; Sofer, Tamar; London, Stephanie J.; Manichaikul, Ani; Hartwig, Fernando P.; Yan, Qi; Artigas, María Soler; Avila, Lydiana; Chen, Wei; Thomas, Sonia Davis; Diaz, Alejandro A.; Hall, Ian P.; et al. (American Thoracic Society, 2018)
Rationale:: Lung function and chronic obstructive pulmonary disease (COPD) are heritable traits. Genome-wide association studies (GWAS) have identified numerous pulmonary function and COPD loci, primarily in cohorts of European ancestry. Objectives: Perform a GWAS of COPD-phenotypes in Hispanic/Latino populations to identify loci not previously detected in European populations. Methods: :GWAS of lung function and COPD in Hispanic/Latino participants from a population-based cohort. We performed replication studies of novel loci in independent studies. Measurements and Main Results: Among 11,822 Hispanic/Latino participants, we identified eight novel signals; three replicated in independent populations of European Ancestry. A novel locus for forced expiratory volume in one second (FEV1) in ZSWIM7 (rs4791658; p=4.99×10-9) replicated. A rare variant (MAF=0.002) in HAL (rs145174011) was associated with FEV1 to forced vital capacity (FEV1/FVC) (p=9.59×10-9) in a region previously identified for COPD-related phenotypes; it remained significant in conditional analyses but did not replicate. Admixture mapping identified a novel region, with a variant in AGMO (rs41331850), associated with Amerindian ancestry and FEV1, which replicated. A novel locus for FEV1 identified among ever smokers (rs291231; p=1.92×10-8) approached statistical significance for replication in admixed populations of African ancestry and a novel SNP for COPD in PDZD2 (rs7709630; p=1.56×10-8) regionally replicated. Additionally, loci previously identified for lung function in European samples were associated in Hispanic/Latino participants in HCHS/SOL at the genome-wide significance level. Conclusions: We identified novel signals for lung function and COPD in a Hispanic/Latino cohort. Including admixed populations when performing genetic studies may identify variants contributing togenetic etiologies of COPD.